A clean method to obtain a porous alumina template - Meier, Lorena Alejandra (2012)
The formation of a porous anodic alumina template using a two-step anodisation process and solutions free of Cr ions was studied. Anodising was conducted under a constant cell potential of 40 V in a 0.3 M oxalic acid electrolyte at 298 K. The chemical dissolution of the first anodising step was carried out in a 2 M phosphoric acid solution, at 298 K. Each step of the template formation was observed by SEM (scanning electron microscopy), evaluating the structural characteristics of the corresponding surfaces. The resulting template has rounded pores (65 nm) that are aligned forming small domains. Although the membrane obtained does not contain fully hexagonal pores, such as those obtained using chromic acid as an attack agent between the two anodising steps, it is equally useful for the finally purpose of producing a template for the growth of nanowires.